Errors in Interpretation of Gram Stain in The First Notification from Positive BACTEC Blood Cultures in Clinical Microbiology Laboratory of Dr. Kariadi Hospital - Maryani, Maryani; Sari, Desvita; Wahyutomo, Ridha; Masfiyah, Masfiyah (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2012)
Background: Blood cultures in conjunction with the initial Gram stain of positive cultures have often been considered the Ã¢â‚¬Å“gold standardÃ¢â‚¬Â for the diagnosis of bacteremia. When blood cultures turn positive, the attending physicians are usually notified immediately about Gram stain findings. However, information on the accuracy of Gram staining is very limited. We examined the error of preliminary blood culture reports provided by a local laboratory in an observational study.Design and Method: This was an observational study with a cross sectional approach. In this study, 369 blood cultures were examined. The positive blood cultures (135 samples) were then examined by Gram stain. Blood cultures handled on Bactec 9050, while the Gram stain was done in standard procedure Gram. Interpretation errors of Gram stain were confirmed by cultures result.Result: During one month (April 2011) we examined 369 blood cultures which 135 are positive (36.5%). Positive blood cultures were misread for 6 (4.4%) of 135 patients, they were two read as gram positive cocci had gram negative organisms by culture which were Acinetobacter baumannii, one read as gram positive bacilli had gram negative bacilli by culture which was Klebsiella pneumoniae. One isolate read as gram negative bacilli had gram positive bacilli which was Bacillus species, while two sample read as gram negative bacilli only had polymicrobial by culture, of these one isolate grew to be Enterobacter aerogenes and Staphylococcus aureus and the other were Escherichia coli and Acinetobacter spp.Conclusion: The overall 4.4% error rate of misinterpreted Gram stains from positive blood culture bottles is relatively high, so laboratory professionals and clinical microbiologist must be aware of the potential types of error that occur (Sains Medika, 4(1):23-29).